MANAJEMEN PENINGKATAN KINERJA GURU - Ahmad Zubair; Rambat Nur Sasongko; Aliman Aliman (Manajer Pendididikan, 2017)
The general objective of this study is to describe the management of increasing teachers’ performance. The specific objectives of this study describe: 1) the planning of the management of increasing teachers’ performance, 2) the implementation of the management of increasing teachers’ performance, 3) the monitoring and evaluation of the management of increasing teachers’ performance and 4) the problems found in the management of increasing teachers’ performance. The research methods of this study was descriptive qualitative and the techniques of data collection were interview, observation and documentation. The research subjects were principal and teachers. The findings of this study show that the planning and the monitoring and evaluation of the management of increasing teachers’ performance runs effectively. But, based on the implementation of the management of increasing teachers’ performance  there are some problems found namely external and internal problems.